New Strait Times , 09 May 2010 (The New Straits Times Press (M) Bhd, 2010)
A strong, pre-dawn earthquake struck eastern Turkey yesterday, killing 51 people as it knocked down stone and mud-brick houses and minarets in at least six villages, the government said.